Proton Pump Inhibitor Use Following Esophageal Variceal Ligation and Its Impact on Clinical Outcomes: Real-World Data from the TriNetX Global Collaborative Network - Nisar Amin; Harleen Chela; Muhammad Faisal Mubarak; Mark Ayoub; Ebubekir Daglilar (Diagnostics)
Background: Proton pump inhibitors (PPIs) are frequently used after endoscopic variceal ligation (EVL) to reduce post-procedural bleeding, though studies have shown mixed results regarding their efficacy. While some suggest benefits, others report no significant advantage and highlight potential risks, including infection, kidney injury, and hepatic complications in cirrhotic patients. This study utilizes the TriNetX global health research network to evaluate the outcomes of PPI use following elective EVL for primary prophylaxis. Methods: This retrospective cohort study was conducted using the TriNetX database to evaluate adult patients with cirrhosis and esophageal varices who underwent EVL for primary prophylaxis. Patients who received at least two weeks of PPI therapy following EVL were compared to those who did not receive PPI within one month post-procedure. Outcomes assessed included esophageal bleeding, adverse events such as acute kidney injury (AKI), pneumonia, spontaneous bacterial peritonitis (SBP), Clostridioides difficile infection, hepatic encephalopathy, and all-cause mortality at 4 weeks and 8 weeks. Results: Of 6196 patients with cirrhosis and esophageal varices who underwent EVL, 12% (n = 764) received adjuvant PPI post-procedure, while 88% (n = 5432) did not receive PPI. After 1:1 propensity score matching, two well-balanced cohorts of 618 patients each were analyzed. PPI use was not associated with a reduction in esophageal bleeding at either 4 weeks (1.8% vs. 1.7%, p = 0.89) or 8 weeks (2.3% vs. 1.9%, p = 0.60). However, the composite adverse event rate—including SBP, hepatic encephalopathy, pneumonia, C. difficile, and acute kidney injury (AKI)—was significantly higher in the PPI group at both 4 weeks (7.9% vs. 3.0%, p < 0.01) and 8 weeks (13.2% vs. 3.0%, p < 0.01). Subgroup analysis showed no significant differences in pneumonia, SBP, or C. difficile infection at either time point. Hepatic encephalopathy was significantly more frequent in the PPI group at 8 weeks (4.9% vs. 2.0%, p = 0.01), and AKI occurred more often at both 4 weeks (5.7% vs. 2.0%, p < 0.01) and 8 weeks (9.6% vs. 2.1%, p < 0.01). Mortality was similar at 4 weeks but significantly higher in the PPI group at 8 weeks (4.3% vs. 1.7%, p < 0.01). Conclusions: PPI use after prophylactic EVL did not reduce bleeding risk and was linked to higher rates of adverse events. These findings suggest routine use may not be beneficial and should be reconsidered in cirrhotic patients who undergo EVL for primary prophylaxis.